Den fraseologiske terminologi - Brink, Lars (Nordiske Studier i Leksikografi, 2006)
The phraseological terminology. The purpose of this paper is to bring law and order to the phraseological terminology. Our current “terminology” is not only systematically undignified, we simply do not understand each other at conferences and the like because it is often impossible to decode the speaker’s terminology and the contents of what he is saying simultaneously. But the worst thing is that thinking is so much influenced by language that as long as our terminology is not well-established, we can hardly do creative empirical research in our field. I go through all the key concepts: phrases which are divided into collocations (divided into open and closed) and idioms (divided into metaphorical and non-metaphorical (further divided into transparent and non-transparent)). All the definitions are listed at the end of the paper. I have tried to avoid idiosyncrasy, by clinging to the best of our traditions.